Analisis Populasi Kehadiran Serangga Berdasarkan Pengaruh Warna Cahaya Di Area Persawahan - Said, Andi Fathir Hidayat; Aulia Rakhmadani; Asmila; Astriya; Syarif Hidayat Amrullah; Hajrah (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2025)
Insects are highly adaptive and diverse invertebrates. Insects are very sensitive to light, especially nocturnal insects. Nocturnal insects are active at night and do many things, such as searching for food, reproducing, and helping to maintain low temperatures. During the day, these insects are unable to do many activities. The purpose of this study was to determine how the color of light affects the presence of insects in rice fields at night. This study used a field experiment method with an experimental design involving three different types of light traps (yellow, blue, and white). Each type of light was tested with three replications of direct observation in the field (rice fields) that had been planted with rice using a light trap. The results showed that the yellow light trap caught the least amount. This shows that the color of light affects the number of nocturnal insects attracted, not the intensity of the light.